Understanding Structure–Function Relationships of Nanoadjuvants for Enhanced Cancer Vaccine Efficacy. (5th January 2022) - Tan, Jia; Ding, Binbin; Teng, Bo; Ma, Ping'an; Lin, Jun
Abstract: Adjuvant, as an important part of vaccines, can observably enhance the magnitude, breadth and durability of immune responses. Nanoadjuvants, as novel vaccine adjuvants, have shown unique advantages and broad application prospects. This review focuses on nanoadjuvants and their structure–function relationships as well as cancer therapy applications. First, different kinds of adjuvants are first introduced and organic/inorganic adjuvants are emphatically listed. Second, the mechanisms of adjuvants are expounded, covering reservoir effect, stimulating dendritic cells (DCs) maturity, enhancing antigen uptake/cross‐presentation, activating complement and inducing cytokines/chemokines release. Next, the methods to evaluate immune effects of adjuvants, including expressions of antigen presenting/costimulatory molecules, detections of T lymphocytes subtypes, antigen‐specific antibodies and cytokine secretion, are summarized. Then the authors emphatically focus on the structure–function relationships of nanoadjuvants, exploring the influence of the size, surface charge, surface ligand, aperture, morphology, and aspect ratio on the immune activities. Finally, the authors briefly discuss the safety of adjuvants and present some representative advances of nanoadjuvants in tumor immunotherapy, photothermal immunotherapy, photodynamic immunotherapy, sonodynamic immunotherapy, chemotherapy or radiotherapy/immunotherapy, chemodynamic immunotherapy and multiple therapies. They hope this review can provide comprehensive understanding and broaden the scopes of nanoadjuvants, thus pave the way to the translation from bench to bedside in the future. Abstract : This review introduces in detail the relationship between the size, aperture, surface charge, surface group, morphology, aspect ratio, and adjuvant activity of nanoadjuvants, and briefly summarizes the classification, mechanisms, evaluation methods, safety, and tumor therapy applications of adjuvants.